2019
DOI: 10.3390/app9030601
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Probiotic Potential of Lactic Acid Bacteria Isolated from Aguamiel and Pulque and Antibacterial Activity Against Pathogens

Abstract: Probiotics can act as a natural barrier against several pathogens, such Helicobacter pylori, a bacterium linked to stomach cancer. The aim of the present study was to isolate and identify lactic acid bacteria (LAB) from pulque and aguamiel, and evaluate their probiotic potential and antimicrobial effect on Escherichia coli, Staphylococcus aureus, and Helicobacter pylori. Ten isolates were selected and evaluated for in vitro resistance to antibiotics and gastrointestinal conditions, and antimicrobial activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
0
13
0
4
Order By: Relevance
“…Lactic and acetic acid production, and thus pH lowering, mainly contributed to the effective inhibition of food-borne pathogen or spoilage microorganism growth in fermented foods (Reis et al 2012 ; Šušković et al 2010 ). The production of organic acids by LAB can inhibit Gram-negative bacteria through the penetration of cell membrane and therefore affecting its functioning, acidifying cytoplasm and inhibiting acid-sensitive enzymes (Cervantes-Elizarrarás et al 2019 ). Another important aspect is the fact that bacterial isolates from later fermentation stages are often characterized by increased organic acid synthesis (Hutkins 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lactic and acetic acid production, and thus pH lowering, mainly contributed to the effective inhibition of food-borne pathogen or spoilage microorganism growth in fermented foods (Reis et al 2012 ; Šušković et al 2010 ). The production of organic acids by LAB can inhibit Gram-negative bacteria through the penetration of cell membrane and therefore affecting its functioning, acidifying cytoplasm and inhibiting acid-sensitive enzymes (Cervantes-Elizarrarás et al 2019 ). Another important aspect is the fact that bacterial isolates from later fermentation stages are often characterized by increased organic acid synthesis (Hutkins 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, 98.3% of the isolates had antibacterial activity against, at least, one food-borne pathogen, and 91.5% of LAB could inhibit the growth of both G − and G + bacteria. Cervantes-Elizarrarás et al found that 60% of isolates from aguamiel and pulque (10 strains) inhibited the growth of E. coli (G − ) and S. aureus (G + ) [36]. An interesting phenomenon was discovered, i.e., L. monocytogenes among all tested pathogens was the most sensitive to the CFS produced by LAB.…”
Section: Discussionmentioning
confidence: 98%
“…and Pediococcus sp. showed antimicrobial activity in vitro against Staphylococcus aureus and Helicobacter pylori (Cervantes-Elizarrarás et al, 2019). Other relevant biological activities have been identified in other bacteria isolated from aguamiel concentrated syrups (agave sap concentrate), including the potential in vitro anticancer enhancement effect of the isolated bacteria Gordonia sp.…”
Section: Potential New Products From Maguey Pulque and Aguamielmentioning
confidence: 99%